PERAN KELUARGA DALAM PENANAMAN NILAI KERUKUNAN ANTAR AGAMA SEJAK ANAK USIA DINI - Atin Risnawati (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
Indonesia is a country that is very rich in ethnicity, class, race and religion. From these differences there must be an attitude of tolerance and harmony between religious groups so that it can become a unifying tool for the nation. From this, the author tries to explain the importance of family figures, especially parents in the planting and teaching of the values of harmony between religious people to children from an early age. Because early age is a period of imitation, therefore families must be able to become role models for children.